Do archives have value? - Moss, Michael; Thomas, David (London Facet Publishing, 2019)
This book will explore ways of establishing and measuring value in the archives and special collections. There is a vast literature about ways of measuring value for cultural heritage assets as a whole, particularly museums and visitor attractions, but archives and special collections in libraries have largely been overlooked. They have been very poor at garnering statistical data and devising ways of measuring the impact of what they do, unlike museums and visitor attractions with their much heavier footfall. Do Archives Have Value? discusses the various valuation methods available, including contingent valuation, willingness to pay and value chain, and assesses their suitability for use by archives and special collections. The book also assesses the impact of the transition to the digital in archival holdings, which will transform their character and will almost certainly cost more. The discussion will be set in the context of changing societal expectations of the archive in the wake of child abuse and other scandals where records to address grievances must be kept irrespective of cost. Value is explored in a range of different cultural and organizational contexts with case studies from a range of countries, including Australia, China, Japan, Malawi, Kenya, Russia and Thailand. There are contributions from Nancy Bell, Head of Conservation at The National Archives, Louise Craven, one of the leading UK archival scholars, Paul Lihoma, National Archivist of Malawi, Helen Morgan from the University of Melbourne, Pak Te Lee of the University of Hong Kong and Richard Wato from the National Archives of Kenya.
Keywords: Archives -- Evaluation -- Great Britain; Archives -- Evaluation